Reconstructing the role of local actors in the Islamization of East Kalimantan - Permata, Ahmad-Norma; Yunani, Ahmad; Burhanudin, Dede; Pinem, Masmedia; Isman, Isman (Indonesian Journal of Islam and Muslim Societies, 2025)
The History of Indonesian Islamization has always been described as a one-way process, where Islam was brought to Indonesia on the initiative of foreign preachers. At the same time, the local community only passively accepted it. This view is typical of colonial scholarship, which stated that Southeast Asian society was backward and could only develop with the help of foreign civilizations. However, archaeological studies challenge this view, which shows that local Southeast Asian society had an advanced life system before the arrival of foreign civilizations. According to these findings, world religions came to Southeast Asia not at the initiative of foreign preachers but were invited by local rulers for local political interests. This study examines the debate between the two approaches in the case of Islamization in the Sultanates of Kutai and Paser in East Kalimantan. This study utilizes a cross-disciplinary corroborative approach, namely archaeological analysis and local politics, to test the mainstream historical narratives. This study found that the Islamization process in East Kalimantan is part of the local centralization of power and regional struggle for political and economic dominance. The study has two significant implications. First, there is a need for criticism of the conventional History of Islamization based on the colonial paradigm. Second, methodological innovation and cross-disciplinary corroboration are needed to revive local history studies, which typically have fragmented sources. Sejarah Islamisasi di Indonesia selama ini selalu digambarkan sebagai proses satu arah, di mana Islam dibawa ke Indonesia oleh dan atas inisiatif pendakwah dari luar. Sementara masyarakat lokal dianggap hanya penerima pasif. Pandangan ini sebenarnya mencerminkan pola pikir kesarjanaan kolonial, yang selalu menganggap masyarakat Asia Tenggara terbelakang dan hanya mampu berkembang dengan bantuan peradaban luar. Namun, kajian-kajian arkeologis kontemporer menunjukkan bukti yang berbeda, yaitu bahwa masyarakat Asia Tenggara sudah memiliki sistem kehidupan yang maju sebelum datangnya pengaruh peradaban-peradaban asing. Menurut temuan ini, agama-agama dunia datang ke Asia Tenggara bukan atas inisiatif pendakwah luar melainkan diundang oleh penguasa-penguasa local untuk kepentingan politik lokal. Riset ini bertujuan menguji perdebatan ini dengan menggunakan kasus sejarah Islamisasi di Kesultanan Kutai dan Paser di Kalimantan Timur. Studi ini menggunakan pendekatan korobortif lintas-disiplin, memadukan pendekatan arkeologis dan pendekatan politik lokal, untuk menguji narasi sejarah mainstream. Ditemukan bahwa proses Islamisasi di Kalimantan Timur merupakan bagian dari proses sentralisasi politik dan pertarungan perebutan dominasi politik dan ekonomi. Temuan kajian ini memiliki dua nilai penting; perlunya sikap kritis terhadap narasi sejarah bercorak kolonialis, dan perlunya inovasi metodologis dan koroborasi lintas-disiplin untuk menghidupkan kajian sejarah lokal yang biasanya sangat miskin sumber-sumber tertulis.